Update on the Anti-Cancer Potency of Tocotrienols and α-Tocopheryl Polyethylene Glycol 1000 Succinate on Leukemic Cell Lines. (14th September 2021) - Constantinou, Constantina; Charalambous, Christiana; Kanakis, Dimitrios; Kolokotroni, Ourania; Constantinou, Andreas I.
Abstract: The natural isoforms of vitamin E γ-tocotrienol (γ-ΤΤ) and δ-tocotrienol (δ-ΤΤ) and the synthetic derivative α-tocopheryl polyethylene glycol 1000 succinate (TPGS) have promising anticancer potency in a variety of cancer cell lines and animal models of cancer. Ongoing clinical trials are investigating the anti-tumor effectiveness of TTs in combination with chemotherapeutic agents in patients suffering from breast, colon, non-small cell lung and ovarian cancers. Despite extensive research on different types of cancer, the anticancer potency of TTs and TPGS has not been thoroughly investigated in leukemias. Given the fact that certain types of leukemias have very low survival rates and that patients suffer significantly from the toxic side effects of chemotherapeutic drugs, there is a need to develop novel treatments with increased specificity against cancer cells and reduced toxicity to the patients. The aim of this review is to report current evidence on the anticancer potency of TTs and TPGS on leukemic cells lines and to discuss future studies that could be carried out to investigate the role of these agents in the management of leukemias.